Relationship of Quaternions and Vector Algebra - Madrakhimova Makhfuza Akhmedovna; Madrakhimov Shukhratjon Shukurovich; Muydinjonov Davlatjon Rafiqjon Ugli; Muydinjonov Ziyodjon Rafiqjon Ugli (Zien Journals, 2022)
In this article applications of quaternion theory to vector algebra are highlighted. The relations between operations on three-dimensional space vectors and calculations on quaternions are given.
Keywords: theory of quaternions; algebra of vectors; quaternion; scalar multiplication